StlcPropProperties of STLC
Require Import Maps.
Require Import Types.
Require Import Stlc.
Require Import Smallstep.
Module STLCProp.
Import STLC.
In this chapter, we develop the fundamental theory of the Simply
Typed Lambda Calculus — in particular, the type safety
theorem.
Canonical Forms
Lemma canonical_forms_bool : ∀t,
empty ⊢ t ∈ TBool →
value t →
(t = ttrue) ∨ (t = tfalse).
Proof.
intros t HT HVal.
inversion HVal; intros; subst; try inversion HT; auto.
Qed.
intros t HT HVal.
inversion HVal; intros; subst; try inversion HT; auto.
Qed.
Lemma canonical_forms_fun : ∀t T_{1} T_{2},
empty ⊢ t ∈ (TArrow T_{1} T_{2}) →
value t →
∃x u, t = tabs x T_{1} u.
Proof.
intros t T_{1} T_{2} HT HVal.
inversion HVal; intros; subst; try inversion HT; subst; auto.
∃x_{0}. ∃t_{0}. auto.
Qed.
intros t T_{1} T_{2} HT HVal.
inversion HVal; intros; subst; try inversion HT; subst; auto.
∃x_{0}. ∃t_{0}. auto.
Qed.
Progress
Proof: By induction on the derivation of ⊢ t ∈ T.
- The last rule of the derivation cannot be T_Var, since a
variable is never well typed in an empty context.
- The T_True, T_False, and T_Abs cases are trivial, since in
each of these cases we can see by inspecting the rule that t
is a value.
- If the last rule of the derivation is T_App, then t has the
form t_{1} t_{2} for some t_{1} and t_{2}, where ⊢ t_{1} ∈ T_{2} → T
and ⊢ t_{2} ∈ T_{2} for some type T_{2}. By the induction
hypothesis, either t_{1} is a value or it can take a reduction
step.
- If t_{1} is a value, then consider t_{2}, which by the other
induction hypothesis must also either be a value or take a
step.
- Suppose t_{2} is a value. Since t_{1} is a value with an
arrow type, it must be a lambda abstraction; hence t_{1}
t_{2} can take a step by ST_AppAbs.
- Otherwise, t_{2} can take a step, and hence so can t_{1}
t_{2} by ST_App2.
- Suppose t_{2} is a value. Since t_{1} is a value with an
arrow type, it must be a lambda abstraction; hence t_{1}
t_{2} can take a step by ST_AppAbs.
- If t_{1} can take a step, then so can t_{1} t_{2} by ST_App1.
- If t_{1} is a value, then consider t_{2}, which by the other
induction hypothesis must also either be a value or take a
step.
- If the last rule of the derivation is T_If, then t = if t_{1}
then t_{2} else t_{3}, where t_{1} has type Bool. By the IH, t_{1}
either is a value or takes a step.
- If t_{1} is a value, then since it has type Bool it must be
either true or false. If it is true, then t steps
to t_{2}; otherwise it steps to t_{3}.
- Otherwise, t_{1} takes a step, and therefore so does t (by ST_If).
- If t_{1} is a value, then since it has type Bool it must be
either true or false. If it is true, then t steps
to t_{2}; otherwise it steps to t_{3}.
Proof with eauto.
intros t T Ht.
remember (@empty ty) as Γ.
induction Ht; subst Γ...
- (* T_Var *)
(* contradictory: variables cannot be typed in an
empty context *)
inversion H.
- (* T_App *)
(* t = t_{1} t_{2}. Proceed by cases on whether t_{1} is a
value or steps... *)
right. destruct IHHt1...
+ (* t_{1} is a value *)
destruct IHHt2...
* (* t_{2} is also a value *)
assert (∃x_{0} t_{0}, t_{1} = tabs x_{0} T_{11} t_{0}).
eapply canonical_forms_fun; eauto.
destruct H_{1} as [x_{0} [t_{0} Heq]]. subst.
∃([x_{0}:=t_{2}]t_{0})...
* (* t_{2} steps *)
inversion H_{0} as [t_{2}' Hstp]. ∃(tapp t_{1} t_{2}')...
+ (* t_{1} steps *)
inversion H as [t_{1}' Hstp]. ∃(tapp t_{1}' t_{2})...
- (* T_If *)
right. destruct IHHt1...
+ (* t_{1} is a value *)
destruct (canonical_forms_bool t_{1}); subst; eauto.
+ (* t_{1} also steps *)
inversion H as [t_{1}' Hstp]. ∃(tif t_{1}' t_{2} t_{3})...
Qed.
intros t T Ht.
remember (@empty ty) as Γ.
induction Ht; subst Γ...
- (* T_Var *)
(* contradictory: variables cannot be typed in an
empty context *)
inversion H.
- (* T_App *)
(* t = t_{1} t_{2}. Proceed by cases on whether t_{1} is a
value or steps... *)
right. destruct IHHt1...
+ (* t_{1} is a value *)
destruct IHHt2...
* (* t_{2} is also a value *)
assert (∃x_{0} t_{0}, t_{1} = tabs x_{0} T_{11} t_{0}).
eapply canonical_forms_fun; eauto.
destruct H_{1} as [x_{0} [t_{0} Heq]]. subst.
∃([x_{0}:=t_{2}]t_{0})...
* (* t_{2} steps *)
inversion H_{0} as [t_{2}' Hstp]. ∃(tapp t_{1} t_{2}')...
+ (* t_{1} steps *)
inversion H as [t_{1}' Hstp]. ∃(tapp t_{1}' t_{2})...
- (* T_If *)
right. destruct IHHt1...
+ (* t_{1} is a value *)
destruct (canonical_forms_bool t_{1}); subst; eauto.
+ (* t_{1} also steps *)
inversion H as [t_{1}' Hstp]. ∃(tif t_{1}' t_{2} t_{3})...
Qed.
Exercise: 3 stars, advanced (progress_from_term_ind)
Show that progress can also be proved by induction on terms instead of induction on typing derivations.Theorem progress' : ∀t T,
empty ⊢ t ∈ T →
value t ∨ ∃t', t ⇒ t'.
Proof.
intros t.
induction t; intros T Ht; auto.
(* FILL IN HERE *) Admitted.
☐
Preservation
- The preservation theorem is proved by induction on a typing
derivation, pretty much as we did in the Types chapter.
The one case that is significantly different is the one for
the ST_AppAbs rule, whose definition uses the substitution
operation. To see that this step preserves typing, we need to
know that the substitution itself does. So we prove a...
- substitution lemma, stating that substituting a (closed)
term s for a variable x in a term t preserves the type
of t. The proof goes by induction on the form of t and
requires looking at all the different cases in the definition
of substitition. This time, the tricky cases are the ones for
variables and for function abstractions. In both, we discover
that we need to take a term s that has been shown to be
well-typed in some context Γ and consider the same term
s in a slightly different context Γ'. For this we
prove a...
- context invariance lemma, showing that typing is preserved
under "inessential changes" to the context Γ — in
particular, changes that do not affect any of the free
variables of the term. And finally, for this, we need a
careful definition of...
- the free variables of a term — i.e., those variables mentioned in a term and not in the scope of an enclosing function abstraction binding a variable of the same name.
Free Occurrences
- y appears free, but x does not, in \x:T→U. x y
- both x and y appear free in (λx:T→U. x y) x
- no variables appear free in \x:T→U. \y:T. x y
Inductive appears_free_in : id → tm → Prop :=
| afi_var : ∀x,
appears_free_in x (tvar x)
| afi_app1 : ∀x t_{1} t_{2},
appears_free_in x t_{1} → appears_free_in x (tapp t_{1} t_{2})
| afi_app2 : ∀x t_{1} t_{2},
appears_free_in x t_{2} → appears_free_in x (tapp t_{1} t_{2})
| afi_abs : ∀x y T_{11} t_{12},
y ≠ x →
appears_free_in x t_{12} →
appears_free_in x (tabs y T_{11} t_{12})
| afi_if_{1} : ∀x t_{1} t_{2} t_{3},
appears_free_in x t_{1} →
appears_free_in x (tif t_{1} t_{2} t_{3})
| afi_if_{2} : ∀x t_{1} t_{2} t_{3},
appears_free_in x t_{2} →
appears_free_in x (tif t_{1} t_{2} t_{3})
| afi_if_{3} : ∀x t_{1} t_{2} t_{3},
appears_free_in x t_{3} →
appears_free_in x (tif t_{1} t_{2} t_{3}).
Hint Constructors appears_free_in.
The free variables of a term are just the variables that appear
free in it. A term with no free variables is said to be
closed.
An open term is one that is not closed (or not known to be
closed).
Exercise: 1 star (afi)
In the space below, write out the rules of the appears_free_in relation in informal inference-rule notation. (Use whatever notational conventions you like — the point of the exercise is just for you to think a bit about the meaning of each rule.) Although this is a rather low-level, technical definition, understanding it is crucial to understanding substitution and its properties, which are really the crux of the lambda-calculus.(* FILL IN HERE *)
☐
Substitution
Proof: We show, by induction on the proof that x appears free
in t, that, for all contexts Γ, if t is well typed
under Γ, then Γ assigns some type to x.
- If the last rule used is afi_var, then t = x, and from the
assumption that t is well typed under Γ we have
immediately that Γ assigns a type to x.
- If the last rule used is afi_app1, then t = t_{1} t_{2} and x
appears free in t_{1}. Since t is well typed under Γ,
we can see from the typing rules that t_{1} must also be, and
the IH then tells us that Γ assigns x a type.
- Almost all the other cases are similar: x appears free in a
subterm of t, and since t is well typed under Γ, we
know the subterm of t in which x appears is well typed
under Γ as well, and the IH gives us exactly the
conclusion we want.
- The only remaining case is afi_abs. In this case t = \y:T_{11}.t12 and x appears free in t_{12}, and we also know that x is different from y. The difference from the previous cases is that, whereas t is well typed under Γ, its body t_{12} is well typed under (Γ, y:T_{11}), so the IH allows us to conclude that x is assigned some type by the extended context (Γ, y:T_{11}). To conclude that Γ assigns a type to x, we appeal to lemma update_neq, noting that x and y are different variables.
Proof.
intros x t T Γ H H_{0}. generalize dependent Γ.
generalize dependent T.
induction H;
intros; try solve [inversion H_{0}; eauto].
- (* afi_abs *)
inversion H_{1}; subst.
apply IHappears_free_in in H_{7}.
rewrite update_neq in H_{7}; assumption.
Qed.
Next, we'll need the fact that any term t that is well typed in
the empty context is closed (it has no free variables).
Exercise: 2 stars, optional (typable_empty__closed)
Corollary typable_empty__closed : ∀t T,
empty ⊢ t ∈ T →
closed t.
empty ⊢ t ∈ T →
closed t.
Proof.
(* FILL IN HERE *) Admitted.
(* FILL IN HERE *) Admitted.
☐
Sometimes, when we have a proof Γ ⊢ t : T, we will need to
replace Γ by a different context Γ'. When is it safe
to do this? Intuitively, it must at least be the case that
Γ' assigns the same types as Γ to all the variables
that appear free in t. In fact, this is the only condition that
is needed.
Lemma context_invariance : ∀Γ Γ' t T,
Γ ⊢ t ∈ T →
(∀x, appears_free_in x t → Γ x = Γ' x) →
Γ' ⊢ t ∈ T.
Proof: By induction on the derivation of
Γ ⊢ t ∈ T.
- If the last rule in the derivation was T_Var, then t = x
and Γ x = T. By assumption, Γ' x = T as well, and
hence Γ' ⊢ t ∈ T by T_Var.
- If the last rule was T_Abs, then t = \y:T_{11}. t_{12}, with T
= T_{11} → T_{12} and Γ, y:T_{11} ⊢ t_{12} ∈ T_{12}. The
induction hypothesis is that, for any context Γ'', if
Γ, y:T_{11} and Γ'' assign the same types to all the
free variables in t_{12}, then t_{12} has type T_{12} under
Γ''. Let Γ' be a context which agrees with
Γ on the free variables in t; we must show Γ' ⊢
\y:T_{11}. t_{12} ∈ T_{11} → T_{12}.
- If the last rule was T_App, then t = t_{1} t_{2}, with Γ ⊢ t_{1} ∈ T_{2} → T and Γ ⊢ t_{2} ∈ T_{2}. One induction hypothesis states that for all contexts Γ', if Γ' agrees with Γ on the free variables in t_{1}, then t_{1} has type T_{2} → T under Γ'; there is a similar IH for t_{2}. We must show that t_{1} t_{2} also has type T under Γ', given the assumption that Γ' agrees with Γ on all the free variables in t_{1} t_{2}. By T_App, it suffices to show that t_{1} and t_{2} each have the same type under Γ' as under Γ. But all free variables in t_{1} are also free in t_{1} t_{2}, and similarly for t_{2}; hence the desired result follows from the induction hypotheses.
Proof with eauto.
intros.
generalize dependent Γ'.
induction H; intros; auto.
- (* T_Var *)
apply T_Var. rewrite ← H_{0}...
- (* T_Abs *)
apply T_Abs.
apply IHhas_type. intros x_{1} Hafi.
(* the only tricky step... the Γ' we use to
instantiate is update Γ x T_{11} *)
unfold update. unfold t_update. destruct (beq_id x_{0} x_{1}) eqn: Hx0x_{1}...
rewrite beq_id_false_iff in Hx0x_{1}. auto.
- (* T_App *)
apply T_App with T_{11}...
Qed.
intros.
generalize dependent Γ'.
induction H; intros; auto.
- (* T_Var *)
apply T_Var. rewrite ← H_{0}...
- (* T_Abs *)
apply T_Abs.
apply IHhas_type. intros x_{1} Hafi.
(* the only tricky step... the Γ' we use to
instantiate is update Γ x T_{11} *)
unfold update. unfold t_update. destruct (beq_id x_{0} x_{1}) eqn: Hx0x_{1}...
rewrite beq_id_false_iff in Hx0x_{1}. auto.
- (* T_App *)
apply T_App with T_{11}...
Qed.
Now we come to the conceptual heart of the proof that reduction
preserves types — namely, the observation that substitution
preserves types.
Formally, the so-called substitution lemma says this:
Suppose we have a term t with a free variable x, and suppose
we've assigned a type T to t under the assumption that x has
some type U. Also, suppose that we have some other term v and
that we've shown that v has type U. Then, since v satisfies
the assumption we made about x when typing t, we can
substitute v for each of the occurrences of x in t and
obtain a new term that still has type T.
Lemma: If Γ,x:U ⊢ t ∈ T and ⊢ v ∈ U, then Γ ⊢
[x:=v]t ∈ T.
Lemma substitution_preserves_typing : ∀Γ x U t v T,
update Γ x U ⊢ t ∈ T →
empty ⊢ v ∈ U →
Γ ⊢ [x:=v]t ∈ T.
One technical subtlety in the statement of the lemma is that
we assign v the type U in the empty context — in other
words, we assume v is closed. This assumption considerably
simplifies the T_Abs case of the proof (compared to assuming
Γ ⊢ v ∈ U, which would be the other reasonable assumption
at this point) because the context invariance lemma then tells us
that v has type U in any context at all — we don't have to
worry about free variables in v clashing with the variable being
introduced into the context by T_Abs.
The substitution lemma can be viewed as a kind of commutation
property. Intuitively, it says that substitution and typing can
be done in either order: we can either assign types to the terms
t and v separately (under suitable contexts) and then combine
them using substitution, or we can substitute first and then
assign a type to [x:=v] t — the result is the same either
way.
Proof: We show, by induction on t, that for all T and
Γ, if Γ,x:U ⊢ t ∈ T and ⊢ v ∈ U, then Γ
⊢ [x:=v]t ∈ T.
Technical note: This proof is a rare case where an
induction on terms, rather than typing derivations, yields a
simpler argument. The reason for this is that the assumption
update Γ x U ⊢ t ∈ T is not completely generic, in the
sense that one of the "slots" in the typing relation — namely the
context — is not just a variable, and this means that Coq's
native induction tactic does not give us the induction hypothesis
that we want. It is possible to work around this, but the needed
generalization is a little tricky. The term t, on the other
hand, is completely generic.
- If t is a variable there are two cases to consider,
depending on whether t is x or some other variable.
- If t = x, then from the fact that Γ, x:U ⊢ x ∈
T we conclude that U = T. We must show that [x:=v]x =
v has type T under Γ, given the assumption that
v has type U = T under the empty context. This
follows from context invariance: if a closed term has type
T in the empty context, it has that type in any context.
- If t is some variable y that is not equal to x, then
we need only note that y has the same type under Γ,
x:U as under Γ.
- If t = x, then from the fact that Γ, x:U ⊢ x ∈
T we conclude that U = T. We must show that [x:=v]x =
v has type T under Γ, given the assumption that
v has type U = T under the empty context. This
follows from context invariance: if a closed term has type
T in the empty context, it has that type in any context.
- If t is an abstraction \y:T_{11}. t_{12}, then the IH tells us,
for all Γ' and T', that if Γ',x:U ⊢ t_{12} ∈ T'
and ⊢ v ∈ U, then Γ' ⊢ [x:=v]t_{12} ∈ T'.
- If t is an application t_{1} t_{2}, the result follows
straightforwardly from the definition of substitution and the
induction hypotheses.
- The remaining cases are similar to the application case.
Proof with eauto.
intros Γ x U t v T Ht Ht'.
generalize dependent Γ. generalize dependent T.
induction t; intros T Γ H;
(* in each case, we'll want to get at the derivation of H *)
inversion H; subst; simpl...
- (* tvar *)
rename i into y. destruct (beq_idP x y) as [Hxy|Hxy].
+ (* x=y *)
subst.
rewrite update_eq in H_{2}.
inversion H_{2}; subst.
eapply context_invariance. eassumption.
apply typable_empty__closed in Ht'. unfold closed in Ht'.
intros. apply (Ht' x_{0}) in H_{0}. inversion H_{0}.
+ (* x<>y *)
apply T_Var. rewrite update_neq in H_{2}...
- (* tabs *)
rename i into y. rename t into T. apply T_Abs.
destruct (beq_idP x y) as [Hxy | Hxy].
+ (* x=y *)
subst. rewrite update_shadow in H_{5}. apply H_{5}.
+ (* x<>y *)
apply IHt. eapply context_invariance...
intros z Hafi. unfold update, t_update.
destruct (beq_idP y z) as [Hyz | Hyz]; subst; trivial.
rewrite ← beq_id_false_iff in Hxy.
rewrite Hxy...
Qed.
intros Γ x U t v T Ht Ht'.
generalize dependent Γ. generalize dependent T.
induction t; intros T Γ H;
(* in each case, we'll want to get at the derivation of H *)
inversion H; subst; simpl...
- (* tvar *)
rename i into y. destruct (beq_idP x y) as [Hxy|Hxy].
+ (* x=y *)
subst.
rewrite update_eq in H_{2}.
inversion H_{2}; subst.
eapply context_invariance. eassumption.
apply typable_empty__closed in Ht'. unfold closed in Ht'.
intros. apply (Ht' x_{0}) in H_{0}. inversion H_{0}.
+ (* x<>y *)
apply T_Var. rewrite update_neq in H_{2}...
- (* tabs *)
rename i into y. rename t into T. apply T_Abs.
destruct (beq_idP x y) as [Hxy | Hxy].
+ (* x=y *)
subst. rewrite update_shadow in H_{5}. apply H_{5}.
+ (* x<>y *)
apply IHt. eapply context_invariance...
intros z Hafi. unfold update, t_update.
destruct (beq_idP y z) as [Hyz | Hyz]; subst; trivial.
rewrite ← beq_id_false_iff in Hxy.
rewrite Hxy...
Qed.
Main Theorem
Proof: By induction on the derivation of ⊢ t ∈ T.
- We can immediately rule out T_Var, T_Abs, T_True, and
T_False as the final rules in the derivation, since in each of
these cases t cannot take a step.
- If the last rule in the derivation is T_App, then t = t_{1}
t_{2}. There are three cases to consider, one for each rule that
could be used to show that t_{1} t_{2} takes a step to t'.
- If t_{1} t_{2} takes a step by ST_App1, with t_{1} stepping to
t_{1}', then by the IH t_{1}' has the same type as t_{1}, and
hence t_{1}' t_{2} has the same type as t_{1} t_{2}.
- The ST_App2 case is similar.
- If t_{1} t_{2} takes a step by ST_AppAbs, then t_{1} =
\x:T_{11}.t12 and t_{1} t_{2} steps to [x:=t_{2}]t_{12}; the
desired result now follows from the fact that substitution
preserves types.
- If t_{1} t_{2} takes a step by ST_App1, with t_{1} stepping to
t_{1}', then by the IH t_{1}' has the same type as t_{1}, and
hence t_{1}' t_{2} has the same type as t_{1} t_{2}.
- If the last rule in the derivation is T_If, then t = if t_{1}
then t_{2} else t_{3}, and there are again three cases depending on
how t steps.
- If t steps to t_{2} or t_{3}, the result is immediate, since
t_{2} and t_{3} have the same type as t.
- Otherwise, t steps by ST_If, and the desired conclusion follows directly from the induction hypothesis.
- If t steps to t_{2} or t_{3}, the result is immediate, since
t_{2} and t_{3} have the same type as t.
Proof with eauto.
remember (@empty ty) as Γ.
intros t t' T HT. generalize dependent t'.
induction HT;
intros t' HE; subst Γ; subst;
try solve [inversion HE; subst; auto].
- (* T_App *)
inversion HE; subst...
(* Most of the cases are immediate by induction,
and eauto takes care of them *)
+ (* ST_AppAbs *)
apply substitution_preserves_typing with T_{11}...
inversion HT_{1}...
Qed.
remember (@empty ty) as Γ.
intros t t' T HT. generalize dependent t'.
induction HT;
intros t' HE; subst Γ; subst;
try solve [inversion HE; subst; auto].
- (* T_App *)
inversion HE; subst...
(* Most of the cases are immediate by induction,
and eauto takes care of them *)
+ (* ST_AppAbs *)
apply substitution_preserves_typing with T_{11}...
inversion HT_{1}...
Qed.
Exercise: 2 stars, recommended (subject_expansion_stlc)
An exercise in the Types chapter asked about the subject expansion property for the simple language of arithmetic and boolean expressions. Does this property hold for STLC? That is, is it always the case that, if t ⇒ t' and has_type t' T, then empty ⊢ t ∈ T? If so, prove it. If not, give a counter-example not involving conditionals.☐
Type Soundness
Exercise: 2 stars, optional (type_soundness)
Put progress and preservation together and show that a well-typed term can never reach a stuck state.Definition stuck (t:tm) : Prop :=
(normal_form step) t ∧ ¬ value t.
Corollary soundness : ∀t t' T,
empty ⊢ t ∈ T →
t ⇒* t' →
~(stuck t').
Proof.
intros t t' T Hhas_type Hmulti. unfold stuck.
intros [Hnf Hnot_val]. unfold normal_form in Hnf.
induction Hmulti.
(* FILL IN HERE *) Admitted.
intros t t' T Hhas_type Hmulti. unfold stuck.
intros [Hnf Hnot_val]. unfold normal_form in Hnf.
induction Hmulti.
(* FILL IN HERE *) Admitted.
☐
Uniqueness of Types
Exercise: 3 stars (types_unique)
Another nice property of the STLC is that types are unique: a given term (in a given context) has at most one type. Formalize this statement and prove it.(* FILL IN HERE *)
☐
Additional Exercises
Exercise: 1 star (progress_preservation_statement)
Without peeking at their statements above, write down the progress and preservation theorems for the simply typed lambda-calculus (as Coq theorems).(* FILL IN HERE *)
☐
and the following typing rule:
Which of the following properties of the STLC remain true in
the presence of these rules? For each property, write either
"remains true" or "becomes false." If a property becomes
false, give a counterexample.
☐
Which of the following properties of the STLC remain true in
the presence of this rule? For each one, write either
"remains true" or else "becomes false." If a property becomes
false, give a counterexample.
☐
☐
Which of the following properties of the STLC remain true in
the presence of this rule? For each one, write either
"remains true" or else "becomes false." If a property becomes
false, give a counterexample.
Which of the following properties of the STLC remain true in
the presence of this rule? For each one, write either
"remains true" or else "becomes false." If a property becomes
false, give a counterexample.
Which of the following properties of the STLC remain true in
the presence of this rule? For each one, write either
"remains true" or else "becomes false." If a property becomes
false, give a counterexample.
Which of the following properties of the STLC remain true in
the presence of this rule? For each one, write either
"remains true" or else "becomes false." If a property becomes
false, give a counterexample.
☐
Exercise: 2 stars (stlc_variation1)
Suppose we add a new term zap with the following reduction rule(ST_Zap) | |
t ⇒ zap |
(T_Zap) | |
Γ ⊢ zap : T |
- Determinism of step
- Progress
- Preservation
☐
Exercise: 2 stars (stlc_variation2)
Suppose instead that we add a new term foo with the following reduction rules:(ST_Foo1) | |
(λx:A. x) ⇒ foo |
(ST_Foo2) | |
foo ⇒ true |
- Determinism of step
- Progress
- Preservation
☐
Exercise: 2 stars (stlc_variation3)
Suppose instead that we remove the rule ST_App1 from the step relation. Which of the following properties of the STLC remain true in the presence of this rule? For each one, write either "remains true" or else "becomes false." If a property becomes false, give a counterexample.- Determinism of step
- Progress
- Preservation
☐
Exercise: 2 stars, optional (stlc_variation4)
Suppose instead that we add the following new rule to the reduction relation:(ST_FunnyIfTrue) | |
(if true then t_{1} else t_{2}) ⇒ true |
- Determinism of step
- Progress
- Preservation
Exercise: 2 stars, optional (stlc_variation5)
Suppose instead that we add the following new rule to the typing relation:Γ ⊢ t_{1} ∈ Bool->Bool->Bool | |
Γ ⊢ t_{2} ∈ Bool | (T_FunnyApp) |
Γ ⊢ t_{1} t_{2} ∈ Bool |
- Determinism of step
- Progress
- Preservation
Exercise: 2 stars, optional (stlc_variation6)
Suppose instead that we add the following new rule to the typing relation:Γ ⊢ t_{1} ∈ Bool | |
Γ ⊢ t_{2} ∈ Bool | (T_FunnyApp') |
Γ ⊢ t_{1} t_{2} ∈ Bool |
- Determinism of step
- Progress
- Preservation
Exercise: 2 stars, optional (stlc_variation7)
Suppose we add the following new rule to the typing relation of the STLC:(T_FunnyAbs) | |
⊢ \x:Bool.t ∈ Bool |
- Determinism of step
- Progress
- Preservation
☐
Exercise: STLC with Arithmetic
To types, we add a base type of natural numbers (and remove
booleans, for brevity).
To terms, we add natural number constants, along with
successor, predecessor, multiplication, and zero-testing.
Inductive tm : Type :=
| tvar : id → tm
| tapp : tm → tm → tm
| tabs : id → ty → tm → tm
| tnat : nat → tm
| tsucc : tm → tm
| tpred : tm → tm
| tmult : tm → tm → tm
| tif0 : tm → tm → tm → tm.
Exercise: 4 stars (stlc_arith)
Finish formalizing the definition and properties of the STLC extended with arithmetic. Specifically:- Copy the core definitions and theorems for STLC that we went
through above (from the definition of values through the
Preservation theorem, inclusive), and paste it into the file at
this point. Do not copy examples, exercises, etc. (In
particular, make sure you don't copy any of the ☐ comments at
the end of exercises, to avoid confusing the autograder.)
- Extend the definitions of the subst operation and the step
relation to include appropriate clauses for the arithmetic
operators.
- Extend the proofs of all the properties (up to preservation) of the original STLC to deal with the new syntactic forms. Make sure Coq accepts the whole file.
(* FILL IN HERE *)
☐